Pengaruh Kualitas Produk, Citra merek dan Word Of Mouth Terhadap Keputusan Pembelian Pada PT Mandiri Apolindo Perkasa - Rubiani, Linda; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2023)
The purpose of this research is to find out how product quality, brand image, and word of mouth influence purchasing decisions. The study sample size was 147 people, all of whom were randomly selected and used a questionnaire to collect information. Furthermore, SPSS version 25 is used to perform statistical analysis such as hypothesis testing, correlation analysis, multiple regression, and examination of classical assumptions and data quality. The test results state that product quality will certainly have a positive and significant effect on purchasing decisions, with a t value of 2.123. Brand image is not able to provide a positive and insignificant influence on purchasing decisions, with the result t count -0.457. word of mouth will certainly have a positive and significant effect on purchasing decisions, with the result t count 4,787. Then simultaneously product quality, brand image, and word of mouth will certainly be able to give an influence on purchasing decisions at PT Mandiri Apolindo Perkasa of 36.8% according to the coefficient of determination data (R2). Based on these test results it can be concluded that product quality is certainly capable of giving a positive and significant impact, brand image does not have a positive and insignificant impact, word of mouth is certainly able to provide a positive and significant, and simultaneously product quality, brand image, and word of mouth. mouth is certainly able to give a positive and significant influence on purchasing decisions at PT Mandiri Apolindo.